Sistem Informasi Kepegawaian Dinas Pendidikan Kepemudaan dan Olahraga (DPKO) Kabupaten Sumba Barat Berbasis Web Menggunakan Framework Laravel - Vanrias Ringu Lango; Adelbertus Umbu Janga; Karolus Wulla Rato (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This research aims to design and implement a web-based personnel information system for the West Sumba Regency Education, Youth and Sports Service (DPKO) using the Laravel framework. This system is designed to make it easier to manage personnel data which includes employee data, attendance, payroll and various other personnel-related information. By utilizing the Laravel framework, this system is expected to be able to provide convenience in managing data efficiently, structured and securely. The use of Laravel was chosen because of its advantages in developing web applications that are fast, safe, and supported by complete features. The results of this research show that the personnel information system being developed can speed up the process of processing employee data, reduce errors in data input, and provide convenience in making data-based decisions. Evaluation of this system was carried out through functionality and performance testing, which showed that this system worked well in accordance with the needs of the West Sumba Regency DPKO.